Simulated Performance of Cross-Laminated Timber Residential Structures Subject to Tornadoes - Stoner, Michael; Pang, Weichiang (Frontiers in Built Environment, 2020)
Tornadoes are some of the most severe and devastating natural events and cause significant damage to structures in the United States. Light-frame wood residential structures have shown vulnerabilities to these events, but they are not explicitly addressed in the design requirements due to their infrequent occurrence, relatively small impact area (compared to hurricanes), and complex wind profile. This paper explores the potential of Cross-Laminated Timber (CLT) to serve as a residential building material, specifically with regards to its performance in tornado events. CLT is an engineered wood product made when orthogonal layers of dimensioned lumber are glued to create panels. To compare the tornado performance of CLT buildings, six archetype residential buildings were each designed using CLT and light-frame wood in accordance to the appropriate US building code provisions and engineering principles. The capacity of each of the structural components was simulated using Monte Carlo Simulation based on the panel spans and connections of the panel boundaries. In addition, the resistance to structure sliding and combined uplift and overturning was simulated using engineering principles based on the load path of a CLT residential structure. Analysis of tornado induced wind loading was performed using recommendations from the 2016 ASCE-7 commentary and applicable literature that attempts to account for the wind-induced pressures caused by tornadoes. Fragility analysis was performed to determine the probability of failure for a given estimated tornado wind-speed. When compared to the wind speeds of the Enhanced Fujita (EF) scale, the CLT residential archetypes showed wind speeds resulting in 10% probability of failure were in the range of EF-4 level events. Factors such as the connection spacing, and roof panel spans had the most significant effect on the simulated performance of the residential archetypes. Thicker panels, more robust connections, or tighter connection spacing could also lead to residential CLT structures that withstand EF-5 level events.